Condutividade elétrica de sementes de diferentes genótipos de feijão - da Silva, Sibelle Santanna; Vieira, Roberval Daiton [UNESP]; Grzybowski, Camila Ribeiro de Souza; de Carvalho, Tereza Cristina; Panobianco, Maristela (FapUNIFESP (SciELO), 2013)
The electrical conductivity test is a fast and non-subjective method used to assess seed physiological potential. Thus, the objective of this study was adapting the methodology for conducting the electrical conductivity test in common bean seeds and investigate effects of genotype in results of the test, comparing cultivars of the two trade groups: Carioca and Black. The study was conducted in two phases: 1- tests with combinations of different temperatures (20, 25, 30, and 35 °C) and five different inhibition periods (4, 8, 16, 20 and 24 h); and 2- assessment of influence of genotype by comparing results obtained on the seeds of both groups. Tests of accelerated aging and seedling emergence in field were also performed. It was concluded that, for seeds of common beans, electrical conductivity test may be performed with samples of 50 seeds per replication, soaked into 75 mL deionized water, incubated at 25 °C, and performing reading of results after 20 or 24 h. It was also concluded that test efficiency is variable according to genotype, and that for the trade group Carioca, there is not genotype effect; although the same results have not occurred for results obtained for the trade group Black.
Electrical conductivity of different common bean seeds genotypes
Keywords: Leaching; Phaseolus vulgaris; Vigor